2019
DOI: 10.1186/s13104-019-4248-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of poor glycemic control among patients with type 2 diabetes on follow-up care at a tertiary healthcare setting in Ethiopia

Abstract: Objective Contemporary clinical guidelines endorsed that glycemic control is the ultimate goal in the management patients with diabetes. The aim of this study was to assess the prevalence of glycemic control and to identify predictors of poor glycemic control in patients with type 2 diabetes (T2D). A cross-sectional study was conducted among systematically selected 357 diabetic patients. Data were collected through direct patients’ interviews and medical chart review. Binary logistic regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
60
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 22 publications
23
60
5
Order By: Relevance
“…This results in increasing difficulty in maintaining glycaemic control, which may explain why a longer duration of diabetes is associated with poorer glycaemic control [28]. The association between poor diabetic medication adherence and poor glycaemic control is consistent with two studies conducted in Tanzania and Ethiopia [29,30]. It has been found that the pain and anxiety associated with daily insulin injections may increase the risk of insulin omission in diabetic patients [31,32].…”
Section: Discussionsupporting
confidence: 58%
“…This results in increasing difficulty in maintaining glycaemic control, which may explain why a longer duration of diabetes is associated with poorer glycaemic control [28]. The association between poor diabetic medication adherence and poor glycaemic control is consistent with two studies conducted in Tanzania and Ethiopia [29,30]. It has been found that the pain and anxiety associated with daily insulin injections may increase the risk of insulin omission in diabetic patients [31,32].…”
Section: Discussionsupporting
confidence: 58%
“…We also found that there was no relationship between the gender of the study participants and glycemic control. In contrast, a study conducted by Harrabi et al [24] in Saudi Arabia reported that being female was associated with poor glycemic control while a study by Demoz et al [55] in Ethiopia also reported that being female was significantly associated with poor glycemic control. One possible reason for this gender difference may be that it is the female who is usually the caregiver for the entire family (including not only the husband and children but also mother and mother-in-law), which might increase her domestic responsibilities.…”
Section: Discussionmentioning
confidence: 85%
“…Socio-demographics included age, sex, ethnicity, income, education, and clinically-related conditions were often found to be predictors of poor adherence [ 5 , 11 , 12 ]. In Ethiopia the rate of poor adherence to anti-diabetes medication is prevalent [ 13 ] and poor adherence is a predictor for poor glycemic control [ 14 ]. The most common reasons for poor adherence include patients not being conscientious with their regimens, patients forgetting to take their medications regularly, and patients stopping when they feel better or worse [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%